Effects of collective leadership on community resilience of relocated informal settlers - Bautista, Teodoro Lloydon C. (Philippine Journal of Public Administration, 2020)
This study explains the influence of collective leadership on community resilience arising from the dislocation of informal settler families (ISFs) relocated in resettlements outside of Metro Manila. This research extends prior literature on collective leadership, social capital, and resilience to crisis, particularly in forced relocation of informal settler families. ISF respondents (n=204) were asked to accomplish a survey to determine the extent of their agreeableness to the predictors of collective leadership—social capital, participatory action, access to socioeconomic resources, and structures and processes for participation—and the predictors’ effect on community resilience. Relationships between these predictor variables on the outcome variable of community’s resilience were analyzed through correlation and three-step hierarchical regression. Results show that social capital and access to socioeconomic resources are strongly associated with community resilience. Meanwhile, the weak to nil relationship between participatory action and community resilience suggests the lack of, and need for, participatory mechanisms that empower ISFs as partners in the resettlement process.